2019
DOI: 10.1080/08037051.2019.1644155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin receptor blockers on blood pressure and renal function in patients with concomitant hypertension and chronic kidney disease: a systematic review and meta-analysis

Abstract: Objective: Angiotensin receptor blockers (ARB) are among the recommended first-line treatment options in patients with hypertension and chronic kidney disease (CKD). This meta-analysis evaluated the effect of ARB on blood pressure (BP) and renal function in patients with concomitant hypertension and CKD with or without diabetes. Methods: Literature search was performed in PubMed/MEDLINE, EMBASE and BIOSIS to identify parallel-group, randomized controlled trials (!8 weeks) reporting the effects of ARB on office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 91 publications
2
13
0
1
Order By: Relevance
“…The lack of differences in food intake, urine output and creatinine clearance between control and losartan-treated rats observed in the current study are also in line with results of previous studies [17][18][19][20][21][22]. Interestingly, we did not observe any differences in serum concentrations and urinary excretions of the electrolytes, albumin and protein between controls and losartan-treated rats (Tables 2 and 3), in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of differences in food intake, urine output and creatinine clearance between control and losartan-treated rats observed in the current study are also in line with results of previous studies [17][18][19][20][21][22]. Interestingly, we did not observe any differences in serum concentrations and urinary excretions of the electrolytes, albumin and protein between controls and losartan-treated rats (Tables 2 and 3), in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…carried out a meta‐analysis on how angiotensin receptor blockers affect the renal function and BP in hypertension patients with CKD. The authors found that after ≥1 year angiotensin receptor blocker monotherapy, proteinuria and hypertension were significantly alleviated (Δproteinuria = −0.90 [95% CI −1.22 to −0.59] g/L, ΔSBP = −14.84 [95% CI −17.82 to −11.85] and ΔDBP = −10.27 [95% CI −12.26 to −8.27] mmHg, P < 0.01), but there were no significant changes in the eGFR 31 . These results were consistent with those of combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…biphenyl carboxylic acid with the empirical formula C33H30N4O2. 24 Telmisartan was the most lipophilic with a log p-value (partition coefficient) of 6.66; followed by Candesartan with a partition coefficient (logP) of 4.02 and valsartan with a partition coefficient of 3.68. Only the lipophilic of the circulating active drug is relevant for tissue penetration after the drug is absorbed.…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 96%